5α‐Reductase type 2 deficiency in families from an isolated Andean population in Venezuela. (15th October 2019) - Avendaño, Andrea; González‐Coira, Mercedes; Paradisi, Irene; Rojas, Ascanio; Da Silva, Gloria; Gómez‐Pérez, Roald; Ceballos, Jesús Osuna
Abstract: 5α‐Reductase type 2 deficiency causes a 46, XY disorder of sex development (DSD) characterized by ambiguous external genitalia, rudimentary prostate, and normal internal genitalia. The disease prevalence worldwide is low, but in a small and isolated village of the Venezuelan Andes, a higher incidence has been found. DNA analysis of the SRD5A2 gene was performed in three inbred affected individuals clinically diagnosed with DSD. The entire coding regions, the p.L89V polymorphism (rs523349) and five intragenic SNPs (rs2300702, rs2268797, rs2268796, rs4952220, rs12470196) used to construct haplotypes were analyzed by Sanger sequencing. To assess the probable ethnic origin of the mutation in this geographic isolate, a population structure analysis was performed. Homozygosis for the p.N193S mutation was found in all patients, with a mutation carrier frequency of 1:80 chromosomes (0.0125) in the geographic focus, suggesting a founder phenomenon. The results of the population structure analysis suggested a mutation origin closer to the Spanish populations, according to the clusters grouping. The genotype–phenotype correlation in the patients was not absolute, being hypospadias and cryptorchidism the main traits that differentiate affected individuals.